The Effect of Problem-Based Learning Integrated with Ethnoscience on Critical Thinking Skills in SMA Negeri 01 Kubu - Mitha Gita Isvida; Ari Sunandar; Hanum Mukti Rahayu (Quagga: Jurnal Pendidikan dan Biologi, 2024)
This research was motivated by the low critical thinking skills of students at SMAN 01 Kubu. The aim of this research is to determine the effect of the model problem-based learning integrated Ethnic on students' critical thinking skills. Sampling uses statistical tests and Effect size. The research sample was students of classes X Mia 1 and X Mia 2 at SMAN 01 Kubu. Data collection uses the Essay test method which refers to Fascione's theory. Based on the research results obtained in the experimental class, the score for the synthesis skills indicator was 71.42%, problem recognition and solving skills 74.28%, evaluation or judging skills 51.42%, analysis skills 80%, and concluding skills 60%. In the control class, scores were for synthesis skills 54.28%, problem recognition and solving skills 14.28%, evaluation or judgment skills 22.85%, analysis skills 60%, and concluding skills 40%. In calculating the effect size, a value of 1.54 was obtained, which is in the very high category.